Peculiar Evolutionary History of miR390-Guided TAS3-Like Genes in Land Plants. (2nd November 2013) - Krasnikova, Maria S.; Goryunov, Denis V.; Troitsky, Alexey V.; Solovyev, Andrey G.; Ozerova, Lydmila V.; Morozov, Sergey Y.
Abstract : PCR-based approach was used as a phylogenetic profiling tool to probe genomic DNA samples from representatives of evolutionary distant moss taxa, namely, classes Bryopsida, Tetraphidopsida, Polytrichopsida, Andreaeopsida, and Sphagnopsida. We found relatives of all Physcomitrella patens miR390 and TAS3-like loci in these plant taxa excluding Sphagnopsida. Importantly, cloning and sequencing of Marchantia polymorpha genomic DNA showed miR390 and TAS3-like sequences which were also found among genomic reads of M. polymorpha at NCBI database. Our data suggest that the ancient plant miR390-dependent TAS molecular machinery firstly evolved to target AP2-like mRNAs in Marchantiophyta and only then both ARF- and AP2-specific mRNAs in mosses. The presented analysis shows that moss TAS3 families may undergone losses of tasiAP2 sites during evolution toward ferns and seed plants. These data confirm that miR390-guided genes coding for ARF- and AP2-specific ta-siRNAs have been gradually changed during land plant evolution.